PENGARUH PERSEPSI HARGA, CITRA MEREK, DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN PADA VIRGIN CAKE & BAKERY CABANG TLOGOSARI - Dzulhanita Melati, 14.05.51.0184; Sutedjo, Bambang (Students' Journal of Economic and Management, 2018)
The study aims to analyze the effect of price perception, brand image, and product quality on customers satisfication. This research was conducted at Virgin Cake & Bakery Tlogosari branch. The population in this study is the customers of Virgin Cake & Bakery Tlogosari branch. The sample in this study were 100 customers using purposive sampling method. Data analysis techniques used include validity tests with KMO (Kaiser Mayer Olkin) and loading factor (component matrix), reliability testing with cronbach alpha, and multiple regression analysis. The result showed that price perception had a positive and significant effect on customer satisfaction, brand image had a positive and significant effect on customer satisfaction, and product quality had no effect on customer satisfaction. Keywords : Price Perception, Brand Image, Product Quality, and Customers Satisfaction